A Monetary Hope for Europe The Euro and the Struggle for the Creation of a New Global Currency - Bosco, Andrea; Guderzo, Massimiliano (Studi e saggi, 2016)
A Monetary Hope for Europe. This book studies the euro in a global perspective and opens a new series edited by the Jean Monnet European Centre of Excellence of the University of Florence, Verso l'unificazione europea. Most of the chapters have been written by economists who met and discussed their diverse views at a multi-disciplinary conference organized by the Centre in May 2013 under the title The euro and the struggle for the creation of a new global currency: Problems and perspectives in the building of the political, financial and economic foundations of the European federal government. The list of contributors also includes historians as well as European and international law academics. Their essays have been revised on the basis and against the backdrop of an ongoing crisis of both the euro and the whole European project in the last years and months. The volume aims to provide useful data and interpretations to improve knowledge on the euro and the European Union in their economic, historical, juridical and political perspectives.